2013
DOI: 10.1074/jbc.m112.384453
|View full text |Cite
|
Sign up to set email alerts
|

Brassinosteroid-regulated GSK3/Shaggy-like Kinases Phosphorylate Mitogen-activated Protein (MAP) Kinase Kinases, Which Control Stomata Development in Arabidopsis thaliana

Abstract: Background: Brassinosteroids (BRs) are plant steroids that signal through the inhibition of GSK3/Shaggy-like kinases such as BIN2. Results: We show here that BIN2 phosphorylates MKK4, which inhibits its activity against MPK6, in a MAPK module that controls stomata patterning. Conclusion: BRs control cellular patterning via BIN2-mediated suppression of MKK4 activity. Significance: Novel cross-talk of GSK3 and MAPK signaling is revealed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
152
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(153 citation statements)
references
References 55 publications
1
152
0
Order By: Relevance
“…Recently, it was demonstrated that BIN2 integrates BR signaling and stomatal development in Arabidopsis (Gudesblat et al, 2012;Kim et al, 2012;Khan et al, 2013). Stomata formed by a pair of guard cells are essential for gas exchange and evaporation of water during photosynthesis and respiration throughout plant life.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was demonstrated that BIN2 integrates BR signaling and stomatal development in Arabidopsis (Gudesblat et al, 2012;Kim et al, 2012;Khan et al, 2013). Stomata formed by a pair of guard cells are essential for gas exchange and evaporation of water during photosynthesis and respiration throughout plant life.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro kinase assays have shown that BIN2 also phosphorylates both MKK4 and MKK5 (Khan et al, 2013). In addition, BIN2 phosphorylation of MKK4 represses its activity against MPK6 in vitro ( Khan et al, 2013; Fig.…”
Section: Bin2 Phosphorylates Several Proteins In Stomatal Signaling Cmentioning
confidence: 99%
“…In addition, BIN2 phosphorylation of MKK4 represses its activity against MPK6 in vitro ( Khan et al, 2013; Fig. 1A).…”
Section: Bin2 Phosphorylates Several Proteins In Stomatal Signaling Cmentioning
confidence: 99%
See 2 more Smart Citations